Phytase immobilization on modified electrodes for amperometric biosensing - Moraes, Marli L.; Oliveira, Osvaldo N.; Rodrigues Filho, Ubirajara P.; Ferreira, Marystela [UNESP] (Elsevier B.V. Sa, 2008)
Phytase (myo-inositol hexaphosphate phosphohydrolase) and phytic acid (myo-inositol hexaphosphate) play an important environmental role, in addition to being a health issue in food industry. Phytic acid is antinutritional due to its ability to chelate metal ions and may also react with proteins decreasing their bioavailability. In this work, we produced biosensors with phytase immobilized in Layer-by-Layer (LbL) films, which could detect phytic acid with a detection limit of 0.19 mmol L-1, which is sufficient to detect phytic acid in seeds of grains and vegetables. The biosensosrs consisted of LbL films containing up to eight bilayers of phytase alternated with poly(allylamine) hydrochloride (PAH) deposited onto an indium-tin oxide (ITO) substrate modified with Prussian Blue. Amperometric detection was conducted in an acetate buffer solution (at pH 5.5) at room temperature, with the biosensor response attributed to the formation of phosphate ions. In subsidiary experiments with the currents measured at 0.0 V (vs. SCE), we demonstrated the absence of effects from some interferents, pointing to a good selectivity of the biosensor. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: biosensor; phytase; amperometric detection; layer-by-layer